Characterization of chicken bone waste-derived hydroxyapatite and its functionality on chitosan membrane for guided bone regeneration - Bee, Soo-Ling; Hamid, Z.A. Abdul (Composites. Part B, Engineering, 2019)
The objective of this research is to prepare asymmetric resorbable membrane based on the hybrid of chitosan (CS) and natural hydroxyapatite (HA) for guided bone regeneration. Briefly, HA with optimum compositional, structural and morphological properties was initially prepared from chicken bone waste via simple calcination. Thereafter, the prepared HA was incorporated into CS to form composite membrane, where the impact of filler loading on the characteristics of resulting membranes were further evaluated. SEM revealed that all composite membranes displayed an asymmetric smooth-rough surface, in which the coarseness of the rough surface increased when the HA content increased. Furthermore, the HA-impregnated membrane exceeding 10 phr loading exhibited improved bioactivity in comparison with pristine sample, being able of developing apatitic layer after 4 weeks of soaking in simulated body fluid. Overall, all membranes degraded less than 22% of the initial weight after 2 months of incubation period, where their degradation rate decrease further as HA loading increase. These findings significantly demonstrate the feasibility of chicken bone-derived HA to be employed as osteogenic filler to augment and tailor the biological characteristics and degradation behaviour of CS membrane for guided bone regeneration. [Display omitted]